Does scapula stabilizing t-shirt help over-head athletes in shoulder discomfort? A randomized control study - Pellegrini, Andrea; Pogliacomi, Francesco; Costantino, Cosimo; Desimoni, Stefano; Giovanelli, Margherita; Golz, Andrew; Tonino, Pietro; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2016)
Scapular dyskinesis in pitchers can potentially lead to impairments in the optimal performance of muscles of the shoulder complex. The purpose of this prospective study was to evaluate whether the use of a scapula stabilizing t-shirt can decrease stress and discomfort in over-head baseball pitchers. Thirty-two semi-professional baseball pitchers were divided into 2 groups. Group A dressed the scapula stabilizing t-shirt during the weekly practice while group B (control group) continued to follow their training program without the t-shirt. All pitchers underwent a clinical examination at the beginning of the study (T0), 4 weeks (T1) and 8 weeks after (T2). Data collected showed a better clinical outcome at T1 which increased in T2 for pitchers in Group A, while in Group B athletes these positive results were not observed. This study underlines that scapula-stabilizing t-shirt can have positive effects on shoulder discomfort in over-head athletes